Mahsa Amini, Hijab, and Mass Movements: Reading the Iranian Constitution About Women in Public Spaces - Mas'odi, Mas'odi; Ahmad, Fandi (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2023)
This study tries to examine the ideology of White Supremacy in the West and its impact on geopolitical stability in several Eastern countries. White Supremacy is an ideology that views the white group as superior to the colored group. This ideology is full of nuances of racism with violent discourse that discredits other groups. Collecting data in this study using literature study. This study aims to examine the process of domination of the West over the East which is full of racism, and the double standard attitude of the West in responding to conflicts in a country. The results of this study show that White Supremacy causes the values of moderation – which are the biological children of democracy – to experience a crisis and do not appear in many Western political policies towards the East. The Israeli-Palestinian conflict, for example, is a concrete example where the West does not sanction Israel, unlike the West did to Russia in the war in Ukraine. This is because Israel and Ukraine are countries that are close to the West, where the right-extreme-radical view is not only widely embraced by the public but also by politicians and government elites.